Etnomatematika dalam Aktivitas Berladang Masyarakat di Kecamatan Tobu - Maldi Rasita Banoet; Wara Sabon Dominikus; Juliana M. H. Nenohai (Universitas Nusa Cendana, 2022)
This study aims to describe mathematics in community farming activities in the Tobu subdistrict and to develop learning tools according to the mathematical concepts found. This research was conducted in Tobu village, Tobu subdistrict with 4 informants. The type of research used is in the form of exploratory qualitive research with an ethnographic design. The results this study indicate that there is ethnomahematics in community farming activities in the Tobu subdistrict in the form of counting, measuring, locating, designing and explaining activities. Mathematical concepts related to community farming activities in the Tobu subdistrict include repeated addition or multiplication, geometry, coordinate systems, number patterns, geometric transformations, comparisons, arithmetic sequences and sets. Thus, various mathematical concepts contained in farming activities can be used as a reference in the development of mathematics learning tools in schools.